Analysis Of Factors Related To Antenatal Care (Anc) Services In Pregnant Women At Waringinkurung Public Health Center - Eva Oktasari; Titin Eka Sugiatini (International Journal of Health and Pharmaceutical (IJHP), 2022)
Antenatal Consideration (ANC) assessment is an effort that saves pregnant women and young people from the causes of gloom and death. The purpose of the ANC is to plan as meticulously and intellectually as possible in order to keep the mom and newborn child pregnant. The requirements related to the contribution of ANC for pregnant women in the Waringinkurung welfare focus strategy were investigated:In the Waringinkurung welfare focus strategy, the described factor is the ANC contribution to pregnant women. Tutoring, data, age, calling, and data sources are all unbiased factors. The survey was used to determine the number of tests from the Slovin section to 83 people. After the facts have been gathered and handled, they will be examined. Results: The study found that the factors associated with providing ANC to young pregnant women at the Waringinkurung polyclinic were ANC contribution (p cost = 0.001), tutoring (p cost = 0.048), information (p cost = 0.030), age (p cost = zero,039), movement (p cost = 0.030), but also source of information (p cost = zero,0.5). The average number of antenatal care visits is several.with the goal of appropriately improving the mother's ability Tips: It is best for pregnant women to have routine pregnancy checks once a month to determine the condition of the mother and baby in the stomach. important phrases: Administration of Ante Natalcare (ANC), preparation, grasp, age, call, and data source.